Overcoming the pains of recovery: the management of negative recovery capital during addiction recovery pathways. (3rd September 2022) - Patton, David; Best, David; Brown, Lorna
Abstract: Recovery is experienced in both positive and negative ways and this paper attempts to integrate the 'pains of desistance' approach into a recovery capital framework. Pains experienced as a result of negative recovery capital are often thought to stimulate motivations for positive behavioral change, usually through a 'rock bottom' type moment. Whilst recovery capital and barriers to recovery have been explored in the literature, conceptualizing these as push and pull factors, and exploring their dynamic interaction, especially at distinct phases of recovery has not. Toward filling these gaps, we use the life-narratives of 30 people in recovery to explore how the pains of recovery (push factors) alongside different forms of recovery capital (pull factors) impact upon and are managed differentially at distinct phases of the recovery journey. Findings indicate the pains of recovery rarely led to positive changes. Rather, a range of pull factors created and promoted positive changes. However, the life narratives reveal that recovery capital cannot be accrued or sustained without managing (eliminating or reducing) the pains of recovery. Overall, this work highlights the need for policy and practice to help reduce the pains of recovery, especially during early recovery to accelerate transition to more stable phases of recovery. As recovery is neither a linear pathway nor a journey without residual challenges for many people, there is much to be learned about effective ongoing management strategies in preventing a return to problematic use that utilize a push and pull framework.